Zakat on LTAT contributions: Ownership, eligibility, and implementation challenges - Nor Paizin, Muhsin; Yasin, Redwan (Journal of Islamic, Social, Economics and Development, 2026)
Malaysian Armed Forces personnel rely heavily on the Lembaga Tabung Angkatan Tentera (LTAT) to secure their post-service financial well-being. However, reconciling these mandatory retirement structures with the religious obligation of zakat presents a complex operational dilemma. This paper investigates the Shariah parameters and institutional frictions surrounding zakat implementation on LTAT contributions. Utilizing a qualitative exploratory design, this study expands on competing fiqh views regarding deferred wealth (mal al-dhimar) and conducts thematic analysis on in-depth interviews with key military and religious stakeholders. The findings indicate that while voluntary savings fit standard zakat frameworks seamlessly, mandatory accounts require a nuanced approach due to structural inaccessibility. To bridge this gap, the paper proposes four operational frameworks, ranging from point-of-withdrawal settlement to automated system integration via wakalah. The study concludes that successful integration demands statutory amendments, inter-agency synergy, and enhanced contributor education to prevent the socio-economic leakage of potential zakat funds.